2024
DOI: 10.1177/10497323231219409
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on Psychosocial Challenges of Patients With Cancer in Ethiopia Using the Social-Ecological Model

Abigiya Wondimagegnehu,
Mathewos Assefa,
Solomon Teferra
et al.

Abstract: Cancer diagnosis and treatment can be physically arduous, disrupting patients’ social and work lives. Understanding the extent of these problems is key to addressing patients’ needs, but specific psychosocial challenges have not yet been well studied in resource-limited settings. A qualitative study was conducted in the capital and two regions of Ethiopia with the aim of exploring psychosocial challenges among cancer patients. A total of 14 in-depth interviews (IDIs) and 16 focus group discussions (FGDs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…[7][8][9]15,24,25 Wondimagegnehu et al found that after the cancer diagnosis, patients have emotional distress, suicidal risk, denial, and refusal of treatment; during the cancer process, patients have hopelessness, depression, and fear of death. 26 In this research, the experiences of breast cancer patients on body image are very interesting. Participants stated that they did not feel like a woman after being diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]15,24,25 Wondimagegnehu et al found that after the cancer diagnosis, patients have emotional distress, suicidal risk, denial, and refusal of treatment; during the cancer process, patients have hopelessness, depression, and fear of death. 26 In this research, the experiences of breast cancer patients on body image are very interesting. Participants stated that they did not feel like a woman after being diagnosed.…”
Section: Discussionmentioning
confidence: 99%